2022
DOI: 10.1159/000523938
|View full text |Cite
|
Sign up to set email alerts
|

The Deep Vascular Plexus Density Is Closely Related to Myopic Severity

Abstract: Objectives: To investigate the relationship between myopic severity and the retinal microvasculature based on quantitative variables using optical coherence tomography angiography (OCTA) and to identify OCTA indicators of microvascular network loss in myopia. Methods: This cross-sectional study included 123 eyes of 123 myopic subjects. The included eyes were divided into three groups according to the spherical equivalent (SE) and axial length (AL): low myopia (LM) (−3.00 D ≤ SE ≤ −0.50 D), moderate myopia (MM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, DCP contributes part of the oxygen demand (10–15%) and nutrition necessary for the inner photoreceptor segments. Hypoperfusion of the DCP may lead to hypoxia and nutritional deficiency in these layers [ 45 , 46 ]. Studies have reported that decreased DCP density was related to the structural impairment in outer retina [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DCP contributes part of the oxygen demand (10–15%) and nutrition necessary for the inner photoreceptor segments. Hypoperfusion of the DCP may lead to hypoxia and nutritional deficiency in these layers [ 45 , 46 ]. Studies have reported that decreased DCP density was related to the structural impairment in outer retina [ 47 ].…”
Section: Discussionmentioning
confidence: 99%